All about you - Anholt, Catherine; Anholt, Laurence (New York : Scholastic, 1991)
Emotions, clothes, houses, animals, family, friends, plays. Children to think about their similarities to, and differences from, other children.
Keywords: Clothing and dress; Emotions; Personality